2015
DOI: 10.1111/jpn.12412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biologically active substances present in water extracts of white mustard and coriander on antioxidant status and lipid peroxidation of mouse C2C12 skeletal muscle cells

Abstract: Coriander and white mustard, an annual plants originated in the Mediterranean region, have been cultivated and used as spices for a long time. Recent studies have shown that they may constitute a potential source of phenolic compounds. The aim of this study was to evaluate the content of polyphenols in coriander and white mustard water extracts and to investigate their antioxidant activity in C2C12 mouse skeletal muscle cells, which serve as a good model of cells with intensive metabolism. HPLC analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…alba could be a potential donor of genetic resistance for biotic disease, environmental stresses, and some other agronomic traits to close relatives such as B. juncea, B. napus and other brassica crops [12,26,27]. Much research has been focused on this wild plant for its medicinal values because of the presence of anti-bacterial, antioxidant, and anti-cancer chemicals [13]. The processed genome sequencing data was not available in any database.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…alba could be a potential donor of genetic resistance for biotic disease, environmental stresses, and some other agronomic traits to close relatives such as B. juncea, B. napus and other brassica crops [12,26,27]. Much research has been focused on this wild plant for its medicinal values because of the presence of anti-bacterial, antioxidant, and anti-cancer chemicals [13]. The processed genome sequencing data was not available in any database.…”
Section: Resultsmentioning
confidence: 99%
“…The plant possesses many important agronomic traits such as tolerance/resistance against Alternaria blight [2,3,4], Sclerotinia stem rot [5], beet cyst nematode [6], flea beetles [7,8], pod shattering [9,10], high temperature [11], and drought [12]. Currently, the importance of this plant has increased due to the identification of antioxidants, antibiotics, and anti-cancer chemicals in its seed extract [13]. The plant can absorb heavy metal (Cd) from the soil, suggesting its potential application in phytoremediation [14].…”
Section: Introductionmentioning
confidence: 99%
“…According to the study carried out by Zielniok et al in white mustard seeds in the largest quantity are present such polyphenols as: catechins (especially catechin and epicatechin) and simple phenolic acids (i.e. ellagic acid, hydroxybenzoic acids and ferulic acid) [30]. These authors have demonstrated, that white mustard polyphenols with high antioxidant activity may have beneficial effects on the muscle tissue (C2C12 mouse skeletal muscle cells) which is characterized with the intensive metabolism, by increasing the concentration of reduced glutathione and upregulating glutathione reductase and peroxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang and his colleagues found that coriander possessed the potential to prevent ultraviolet radiation-induced skin photoaging [21]. More importantly, coriander extracts have been used to scavenge ROS as well as up-regulate endogenous cellular antioxidant systems [22,23]. These findings suggest that coriander may act as a radioprotective agent to mitigate IR-induced hematopoietic injury due to its antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%